Islamic-Nuanced Mathematics Teaching Material: An Alternative Tool to Improve Students' Understanding on Integers - Rauzah, Rauzah; Vitoria, Linda (Jurnal VARIDIKA, 2023)
The acquisition of mathematical proficiency among university students, particularly within the Department of Elementary Education at Universitas Syiah Kuala, Aceh – Indonesia, often presents challenges. Integrating religious undertones into mathematics pedagogy represents a constructive approach to engender student engagement and augment comprehension. Such integration affords students a familiar contextual backdrop, fostering a more meaningful learning milieu. This article delineates the development of an instructional resource imbued with Islamic motifs, specifically addressing concepts related to integers. The study cohort comprises 115 second-year students enrolled in the Department of Elementary Education at Universitas Syiah Kuala. Methodological stages encompassed preliminary inquiry, developmental endeavors, and evaluative assessments. Research instrumentation encompassed validation protocols for assessing integrity and observation metrics capturing students' instructional engagements. Additionally, assessments, accompanied by post-instructional questionnaires, were administered to gauge student perceptions. Qualitative data analyses were conducted, evaluating the product's viability across dimensions of validity, applicability, and efficacy. Iterative revisions were undertaken during the instructional resource's refinement process. Outcomes underscore the aptness of the Islamic-imbued mathematics instructional material for second-year students within the elementary education domain. The implications of these findings underscore the advantages conferred by familiar-contextualized learning materials in facilitating students' mathematical comprehension.